Exact path delay fault coverage with fundamental ZBDD operations. - Padmanaban, S. (IEEE Transactions on computer-aided design of integrated circuits and systems)
We formulate the path delay fault (PDF) coverage problem as a combinatorial problem that amounts to storing and manipulating sets using a special type of binary decision diagrams, called zero-suppressed binary decision diagrams (ZBDD). The ZBDD is a canonical data structure inherently having the property of representing combinational sets very compactly. A simple modification of the proposed basic scheme allows us to increase significantly the storage capability of the data structure with minimal loss in the fault coverage accuracy. Experimental results on the ISCAS85 benchmarks show considerable improvement over all existing techniques for exact PDF grading. The proposed methodology is simple, it consists of a polynomial number of increasingly efficient ZBDD-based operations, and can handle very large test sets that grade very large number of faults.